The leftovers. The complete third season [videorecording (DVD)] - Theroux, Justin; Brenneman, Amy; Eccleston, Christopher; Tyler, Liv; Zylka, Chris, 1985-; Duncan, Lindsay; Adepo, Jovan; Carroll, Kevin; King, Regina; Qualley, Margaret; Dowd, Ann; Coon, Carrie, 1981-; et al. (Leftovers (Television program)., 2017)
Adaptation of Tom Perrotta's novel about life in a small town after many of its residents vanished in a Rapture-like event. In the third season, the Garvey and Murphy families come together as they desperately grasp for a system of belief to better explain what defies explanation. The world is crackling with the energy of something big about to happen, a corresponding bookend to the Sudden Departure that sent them all spinning years earlier, bringing their journey Down Under.